Excellent Microwave Absorption Properties in the C Band for the Nitrided Y2Fe12Co4Si/Paraffin Composites - Wenjian Tang; Hanxing Xu; Xichun Zhong; Na He; Zhongwu Liu; Raju V. Ramanujan (Magnetochemistry, 2025)
The nitriding process was employed to optimize the low-frequency microwave absorption properties of Y2Fe12Co4Si/paraffin composites. The effects of nitriding temperature on the phase composition, static magnetic properties, electromagnetic parameters, and microwave absorption performance were systematically investigated. As the nitriding temperature increases, lattice expansion results in a significant increase in saturation magnetization and a higher ratio of in-plane to out-of-plane anisotropy fields. This, in turn, boosts the electromagnetic parameters of the composite material. With a further rise in temperature, an increased content of α-Fe is produced and the ratio of the in-plane to out-of-plane anisotropy field diminishes, leading to a decline in electromagnetic parameters. At 500 °C, these factors reach an optimum level, maximizing the composite’s electromagnetic parameters. The composite exhibited a minimum reflection loss (RLmin) of −55.9 dB at 5.58 GHz with a thickness of 2.46 mm. Moreover, at a thickness of 2.21 mm, the composite achieved a maximum effective absorption bandwidth (EABmax) of 2.95 GHz (5.05–8 GHz). Compared with other low-frequency-absorbing materials, the composite exhibited stronger absorption and a wider absorption bandwidth at a lower thickness in the C band.